The role of BH3-only protein Bim extends beyond inhibiting Bcl-2–like prosurvival proteins - Mérino, Delphine (The Rockefeller University Press, 2009)
Proteins of the Bcl-2 family are critical regulators of apoptosis, but how its BH3-only members activate the essential effectors Bax and Bak remains controversial. The indirect activation model suggests that they simply must neutralize all of the prosurvival Bcl-2 family members, whereas the direct activation model proposes that Bim and Bid must activate Bax and Bak directly. As numerous in vitro studies have not resolved this issue, we have investigated Bim's activity in vivo by a genetic approach. Because the BH3 domain determines binding specificity for Bcl-2 relatives, we generated mice having the Bim BH3 domain replaced by that of Bad, Noxa, or Puma. The mutants bound the expected subsets of prosurvival relatives but lost interaction with Bax. Analysis of the mice showed that Bim's proapoptotic activity is not solely caused by its ability to engage its prosurvival relatives or solely to its binding to Bax. Thus, initiation of apoptosis in vivo appears to require features of both models.